A comparison between the apical and subcostal view for three-dimensional echocardiographic assessment of right ventricular volumes in pediatric patients - Ferraro, Alessandra M.; Bonello, Kristin; Sleeper, Lynn A.; Lu, Minmin; Shea, Melinda; Marx, Gerald R.; Powell, Andrew J.; Geva, Tal; Harrild, David M. (Frontiers in Cardiovascular Medicine, 2023)
Background: Accurate measurement of ventricular volumes is an important clinical imaging goal. Three-dimensional echocardiography (3DEcho) is used increasingly as it is more available and less costly than cardiac magnetic resonance (CMR). For the right ventricle (RV), the current practice is to acquire 3DEcho volumes from the apical view. However, in some patients the RV may be better seen from the subcostal view. Therefore, this study compared RV volume measurements from the apical versus the subcostal view, using CMR as a reference standard. Methods: Patients <18 years old undergoing a clinical CMR examination were prospectively enrolled. 3DEcho was performed on the day of the CMR. 3DEcho images were acquired with Philips Epic 7 ultrasound system from apical and subcostal views. Offline analysis was performed with TomTec 4DRV Function for 3DEcho images and cvi42 for CMR ones. RV end-diastolic volume and end-systolic volume were collected. Agreement between 3DEcho and CMR was assessed with Bland-Altman analysis and the intraclass correlation coefficient (ICC). Percentage (%) error was calculated using CMR as the reference standard. Results: Forty-seven patients were included in the analysis (age range 10 months to 16 years). The ICC was moderate to excellent for all volume comparisons to CMR (subcostal vs. CMR: end-diastolic volume 0.93, end-systolic volume 0.81; apical vs. CMR: end-diastolic volume 0.94, end-systolic volume 0.74).The 3DEcho mean % error vs. CMR for end-systolic volume was 25% for subcostal and 31% for apical; for end-diastolic volume it was 15% for subcostal and 16% for apical. The % error was not significantly different between apical vs. subcostal views for end-systolic and end-diastolic volume measurements. Conclusions: For apical and subcostal views, 3DEcho-derived ventricular volumes agree well with CMR. Neither echo view has a consistently smaller error when compared to CMR volumes. Accordingly, the subcostal view can be used as an alternative to the apical view when acquiring 3DEcho volumes in pediatric patients, particularly when the image quality from this window is superior.